The dynamics of trade diversion: Observations on West Germany's integration into the Little European Common Market 1958-1972 - Holger Schmieding (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1988)
In the postwar history of Western Europe, the period from 1958 to 1972 stands out as the time of the economic division of this part of the world into two trading blocs: the European Economic Community (EEC), established in 1958, and the European Free Trade Association (EFTA), formed two years later. Before 1958, institutions dealing with the entire region had helped to shape trade policy in Europe; after 1972, the two trading blocs fused into one as all EFTA countries either joined the EEC or concluded free-trade agreements with the Community. This paper investigates some of the causes and consequences of the EEC-EFTA rift in the 1960s, focusing on the role played by Germany, i.e., the country which, of all EEC members, had the closest trade links to countries across the divide. Therefore, we will sketch out some arguments of the theory of regional liberalisation (Chapter II), discuss the major determinants of the actual German trade policy in the 1950s and 1960s (Chapter III), assess the impact of the economic division of Western Europe on Germany's foreign trade (Chapter IV). The concluding remarks (Chapter V) will take up the question whether Germany's integration into a little Europe and the parallel economic division of Western Europe were a necessary stage on the way towards freer trade in this part of the world or a costly detour.
Keywords: 330